Synthesis of telechelic anthraquinone‐functionalized polybutadiene via ROMP and study of its photo‐oxidation and UV crosslinking behaviors. Issue 12 (31st March 2018) - Lee, Jeonghyun; Moon, Bongjin
ABSTRACT: Telechelic anthraquinone‐functionalized polybutadiene (AQ‐PB‐AQ) was synthesized by ring opening metathesis polymerization to achieve homogeneous dispersion of AQ groups in the polymer matrix. It was observed that the AQ end groups act as a sensitizing group resulting in photo‐induced crosslinking and oxidation reaction at the olefin groups in the PB. The process was confirmed by comparing the polymer's mass loss and Fourier transform infrared (FTIR) spectra with those of telechelic diacetoxy‐functionalized PB (AcO‐PB‐OAc) which did not show any difference before and after ultraviolet irradiation. Homogeneity of the AQ groups in PB matrix results in rapid crosslinking of PB in a short period of time (<4 min) while a simple blend of AQ methyl ester in AcO‐PB‐OAc matrix did not show such behavior. Photo‐oxidative reaction has concurrently occurred during the crosslinking reaction. Generation of OH, OOH, and carbonyl groups in the matrix during the photo‐oxidation was verified by FTIR, elemental analysis, and water contact angle measurements. A plausible mechanism for the process was proposed in which the photo‐sensitized AQ groups abstract hydrogen from the PB chain to yield reactive radical species, initiating oxidative crosslinking, and degradation of PB or reduction of AQ to hydroanthraquinone species. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1249–1258 Abstract : Telechelic anthraquinone‐functionalized polybutadiene (AQ‐PB‐AQ) was synthesized via ROMP to achieve homogeneous dispersion of anthraquinone moieties in the polymer matrix. The photochemical reactions taking place in the polymer matrix under UV irradiation were investigated by FTIR spectroscopy, differential scanning calorimetry (DSC), elemental analysis, and contact angle measurement. Homogeneity of the anthraquinone groups leads to rapid crosslinking of PB under UV irradiation. Significant photo‐oxidation also occurred on the polymer backbones making them more hydrophilic.